Penentuan Titik Tetap dan Matriks Jacobi Model Matematika Strategi Pengendalian Kebakaran Hutan - Emilia Juliyanti Bria; Elinora Naikteas Bano; Dicky Frengky Hanas (Program Studi Matematika, Universitas Timor, 2022)
Forest is one of the assets owned by the community around the forest. Forest destruction is a problem for communities around the forest who depend on available forest resources every day for their lives. The purpose of this research is to look at the dynamics of forest resource destruction and its control strategies. The model equation obtained is a system of non-linear differential equations, from the system then fixed point and Jacobi matrix are determined. From the analysis results, seven fixed points are obtained, then the Jacobi matrix is determined from each fixed point.